Receipt of prescription opioid medication is associated with increased mortality in an Israeli population - Matan J. Cohen; Reuven L. Dressler; Ehud Kaliner (BMC, 2024)
Abstract Background Despite Israel's increased use of prescription opioids, reported deaths resulting or associated with opioids have decreased, in fact dramatically, since 2005. This contrast is unique and difficult to explain. We sought to examine whether higher prescribed opioid dosages among adults without oncologic diagnoses were associated with higher all-cause mortality rates. Methods A historical cohort study in Clalit Health Services, using a data repository including all adult patients prescribed opiates between 2010 and 2020, excluding patients with oncologic diagnoses. Patients were classified into three groups according to opioid use: below 50 Morphine milligram equivalents (MME) per day, 50 to 90 MME per day, and above 90 MME per day. Sex, Charlson comorbidity score, age and socioeconomic status were recorded. Mortality rates were compared between the dosage groups and compared to age-standardized mortality rates in the general population. Results On multivariate analysis, patients receiving 90 or more MME per day were 2.37 (95%CI 2.1 to 2.68) more likely to have died compared to patients receiving below 50 MME per day. The respective hazard ratio among patients receiving between 50 and 90 MME per day was 2.23 (2.01 to 2.46). Among patients aged 18 to 50, standardized mortality ratios (SMRs) compared to the general population ranged between 5.4 to 8.6 among women, receiving between 50 and 90 MME per day, and between 8.07 and 10.7 among women receiving 90 or more MME per day. The respective SMRs among men were 1.2 to 3.8 and 2.7 to 5.4. Conclusion Increased opioid use is independently associated with increased all-cause mortality among non-oncological patients. This result is most notable among young adults with little or no known comorbidities. These findings are consistent with results in other countries and seem more credible than previous Israeli reports. Healthcare regulators and providers should, therefore, act to curtail the increasing opioid prescriptions and devise and enhance controls in the healthcare system, which, until 2020, had very limited mechanisms in place.